The Contribution of Three Pillars: Government, Community, and Students in Establishing Sustainable Development Goals (SDGs) in Timor-Leste - Conceição, Florencia da (Journal of Economics and Business UBS, 2025)
The purpose of this research is to find out how Government, Community, and Students of Timor-Leste understand and aware towards SDGs. By knowing this, we can know what they do not understand and create better learning programs so that they can participate in achieving sustainable development goals. The research method used in this research is qualitative method. The study collected both primary and secondary data. In this study, the researcher sought to comprehensively explore the contributions made by the government, civil society, and students in Timor-Leste in an effort to achieve the Sustainable Development Goals (SDGs) that have been set for 2030. This investigation aims to deeply analyze the roles and synergies between these three key actors in the context of national sustainable development. Based on the findings and analysis of this research, it can be concluded that the commitment to the achievement of the Sustainable Development Goals (SDGs) in Timor-Leste is not only shown by the government, but also reflected in the active involvement of the community and students. The Government of Timor-Leste has shown a strong commitment through the ratification of various regulations and the establishment of institutions that support the implementation of the SDGs